Emergence of High Prevalence of Extended-Spectrum Beta-Lactamase and Carbapenemase-Producing Enterobacteriaceae Species among Patients in Northwestern Ethiopia Region. (4th February 2022) - Tadesse, Selamyhun; Mulu, Wondemagegn; Genet, Chalachew; Kibret, Mulugeta; Belete, Melaku Ashagrie
Abstract : Background . World Health Organization identified some Enterobacteriaceae as superbugs because of their high production and spread of extended-spectrum beta-lactamases (ESBL) and carbapenemases. Moreover, their resistance against commonly prescribed antibiotics left few choices of drugs to treat infection. This study is aimed at determining the magnitude of ESBL and carbapenemase-producing Enterobacteriaceae pathogens and their antimicrobial resistance pattern. Materials and Methods . A hospital-based cross-sectional study was carried out from February to April 2019 in the Northwestern Ethiopia region. A total of 384 patients presumptive for bacterial infections were conveniently enrolled in the study. Specimens were collected and processed following standard bacteriological procedures. Drug susceptibility tests were performed using disk diffusion technique. ESBL and carbapenemase enzymes were tested by double disk diffusion and modified carbapenem inhibition methods, respectively. The data obtained were analyzed using SPSS version 22 software, and descriptive statistics were summarized in tables and graphs. Results . Out of 384 clinical specimens processed 100 (26%) were culture positive for Enterobacteriaceae . The proportion of Enterobacteriaceae infection was relatively higher among in-patients 86 (32.6%) than out-patients 14 (11.7%). Overall, Escherichia coli 35 (9.1%) was the leading isolate followed by Klebsiella pneumoniae 31 (8.1%). Klebsiella pneumoniae 15 (15.6%) was the most frequent isolate from bloodstream infection and is the leading isolate from intensive care unit patients 15 (38.3%). Overall, 44 (44%) of Enterobacteriaceae were extended-spectrum beta-lactamase producers. Among them, Citrobacter spp. was the leading one 4 (80%) followed by Enterobacter cloacae 6 (60%) and K . pneumoniae 18 (58.1%). Furthermore, 6 (6%) of Enterobacteriaceae were carbapenemase-producers, in which 5 (50%) of E . cloacae and 3 (9.7%) of K . pneumoniae had highest percentage . Conclusions . ESBL and carbapenemase-producing isolates of Enterobacteriaceae are alarmingly spreading in the study area. Thus, improving the infection prevention strategy and further screening at the national level is recommended to develop the optimal use of antibiotics.